Circular economy practices by upcycling waste product creation at local coffee shop - Nazwa, Nubzatu; Setiyorini, Heri; Gitasiswhara, Gitasiswhara (Universitas Widya Mataram, 2025)
The swift expansion of Indonesia's coffee sector has led to rising environmental issues, especially concerning coffee grounds and plastic waste. This research investigates the ways in which local coffee shops adopt circular economy principles via upcycling efforts that transform waste into useful products. Employing a qualitative case study method with 21 participants, comprising both managers and consumers, the data were thematically analyzed to uncover significant patterns of circular practices. The findings highlight three primary themes: (1) Circular Economy Principles, which focus on reducing waste, substituting eco-friendly materials, and implementing standardized waste management systems;(2) The Waste Transformation Process includes a five-stage upcycling workflow and cooperative partnerships with local MSMEs to handle 1.8–3.5 tons of waste each month; and (3) Upcycling Product Creation phase, where waste materials are converted into unique and visually appealing products like eco-bags, coffee soap, and furniture panels. These initiatives not only minimize waste but also generate social and economic benefits through community empowerment. In summary, this study illustrates that local coffee shops can function as micro-laboratories for sustainability, merging environmental accountability, creative innovation, and inclusive circular economy practices.